Influence of the thermomechanical loading on the behavior of high performance concrete and ordinary concrete - Moulaï Abdellah Bouabdallah (Journal of Building Materials and Structures)
The present article aims to present an experimental study to investigate the behavior of high performance concrete and ordinary concrete that were subjected to thermomechanical loading. The mechanical properties of both types of concrete, which underwent heat treatment, were studied at room temperature. In addition, the compressive strength was tested and calculated at different ages, namely 7, 14, 28 and 60 days. For each test, the samples were heated at a rate of 5 °C/min, until the following temperatures were reached, i.e. 250 °C, 350 °C, 450 °C, 600 °C and 900 °C. The target temperature was kept constant for one hour in order to ensure that it was uniform throughout the sample, before cooling. Moreover, the sample weight was measured before and after heating in order to determine the weight loss of the samples tested. The findings allowed concluding that the mechanical characteristics of concrete were enhanced after exposure to temperatures within the range from 250 °C to 450 °C.